Subtitling the Sacred: Navigating Strategies and Challenges in Subtitling Religious Content - Al-Shlool, Safaa (International Journal of Linguistics and Translation Studies, 2025)
Subtitling religious content, particularly sacred texts, presents complex challenges within audiovisual translation, requiring a careful balance between linguistic fidelity, cultural sensitivity, and technical constraints. This study explores the hurdles faced by subtitlers when working with religious material and examines the strategies they employ to navigate these challenges. A survey was conducted to gather insights into the nuanced practices of subtitlers across various audiovisual genres. The survey was distributed via professional networks on Facebook, targeting specialised groups with memberships ranging from 10,000 to over 100,000, and through direct outreach on LinkedIn. Despite efforts to encourage participation through anonymity, the response rate was limited, with only 28 subtitlers completing the survey. The findings reveal that subtitlers prioritise linguistic accuracy while employing strategies such as literal translation, compensation, transposition, and omission to handle the complexities of religious content. Participants identified challenges in preserving meaning and addressing culturally or theologically sensitive material. These challenges are classified into intrinsic factors, such as the theological and linguistic nuances of the source text, and external influences, including technical constraints, media platforms, media genre, censorship policies, audience perspectives, and subtitlers’ own perspectives. Moreover, the study highlights a significant gap in formal guidelines for subtitling religious content, leaving subtitlers to rely heavily on their professional judgement, expertise, and personal discretion. This research offers valuable insights that can inform the development of specialised training and standardised practices in this critical yet underexplored field of audiovisual translation.